Implementasi Nilai Pendidikan Karakter Pada Budaya Sekolah di SD Kristen Makale 2 - Novalia Sulastri (LPPM UKI Toraja, 2022)
The background of this problem is the Implementation of Character Education Values in School Culture in Makale Christian Elementary School 2 Makale. This research aims to find out how the application of character education value to school culture in Makale Christian Elementary School 2. This type of research is to use descriptive qualitative method research, with this type of case study research. The subjects in this study were students from grade I-VI of Makale Christian Elementary School 2. While the object of this research is the value of character education on school culture. Research instruments used are interviews, questionnaires, observations and documentation. The results of this study show that the application of the value of character education to school culture is carried out well which can be seen from the 7 application of character education values, including honesty, discipline, responsibility, care, cooperation, care and courtesy.